New Assessment Model of Financing Treatment of Patients with Complete Tooth Loss - Grachev, Dmitry I.; Martynenko, Aleksandr V.; Perekhodov, Sergey N.; Kostyrin, Evgeniy V.; Mustafaev, Magomet Sh.; Akhmedov, Kamalutdin G.; Deshev, Aslan V.; Rozanov, Daniil G.; Korotkova, Nadezhda L.; Kerasov, Stefan N.; Arutyunov, Sergey A. (Ital Publication, 2024)
According to the World Health Organization, the global prevalence of complete tooth loss is estimated to be 7% among individuals aged 20 years and older, while for those aged 60 and over, this rate significantly increases to 23%. This study is relevant due to the psychological trauma, social challenges, and functional limitations caused by tooth loss, as well as the uneven availability of dental care worldwide. The goal of this research is to develop and implement a new model to assess the socioeconomic feasibility of investing in digital technologies for diagnosing and treating patients with complete tooth loss using removable polymer prostheses produced through additive 3D printing. The study employs scenario analysis, the clustered rankings coordination method, statistical methods, expert opinion assessment using Kendall’s coefficient of rank concordance, system analysis and design, questionnaires, sociometry, and functional modeling. The practical significance of this research lies in providing a quantitative assessment of economic opportunities for effectively using RPDs in three groups: RPDs without additional fixation means; those with special adhesive agents for improved fixation; and implant-supported prosthetics with conditionally removable dentures similar to RPDs. The scientific novelty of this study is the development of a new evaluation model that justifies the choice of prosthetic treatment technology for patients with complete tooth loss, enabling the most rational use of resources. Doi: 10.28991/ESJ-2024-08-05-014 Full Text: PDF